HAK KONSTITUSIONAL BURUH PEREMPUAN DALAM BINGKAI NEGARA HUKUM KESEJAHTERAAN DI INDONESIA - Triana Sofiani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
This study just want to expose on the constitutional rights of women workers in Indonesia within the legal framework of the welfare state. Indonesia as a state welfare law, of course, the duty to enforce the welfare of all citizens, both men and women without discrimination, including the constitutional rights of women workers. The state is obliged regulate wages, provide protection, social security and guarantee of other rights, fairly and without discrimination in accordance constitutional rights of women workers as the provisions contained in the Constitution of the Republic of Indonesia 1945.